(untitled) (Ius Novum, 2022)
The subject of the gloss is a resolution of the Supreme Administrative Court in which the Court examined the rules of determining income in social assistance proceedings. While recognising the possibility of reducing income solely by the amount of alimony provided to an entitled person under the provisions of the family and guardianship code, the Supreme Administrative Court stated unequivocally that the privileged method of determining income cannot be used by persons who do not pay alimony and are obliged to make payments to the alimony fund. This gloss presents arguments supporting the theses contained in the resolution and their axiological justification. Moreover, it elaborates on the issues indirectly raised by the adjudicating panel, such as overdue alimony and amounts that are actually paid as part of alimony. This subject is important for determining the income of persons applying for support under the social assistance system as well as paying for benefits.